Spatiotemporally light controlled "drug-free" macromolecules via upconversion-nanoparticle for precise tumor therapy. (February 2022) - Wang, Jun; Qi, Jing; Jin, Feiyang; You, Yuchan; Du, Yan; Liu, Di; Xu, Xiaoling; Chen, Minjiang; Shu, Gaofeng; Zhu, Luwen; Ying, Xiaoying; Ji, Jiansong; et al.
Highlights: 1. A novel abiotic polymer chemistry in living system. 2. Clustering cell-surface receptors and thus manipulating cell fate by a NIR-light controlled polymerization. 3. The bio-application of in-situ synthesized nano-materials has been expanded. 4. A drug-free macromolecular anti-tumor therapeutic. Graphical Abstract: Schematic illustration of the NIR up-conversion controlled, in-situ synthesized, drug-free macromolecular therapeutic for anti-tumor therapy. ga1 Abstract: Drug-free macromolecular therapeutics induce cell apoptosis by clustering non-internalizing cell-surface receptors, which has demonstrated great promise in tumor therapy, particularly in terms of non-specific toxicities when compared with low-molecular-weight drugs. However, most reported drug-free macromolecular therapeutics involve a 'two-step' administration manner and the in vivo study is scarce, likely imposing difficulties on in vivo application. Here, we in-situ synthesized a drug-free macromolecular therapeutic in living system by near-infrared up-conversion controlled cross-linking. Taking CD20 receptor-positive B-cell lymphoma as the model disease, poly(2-hydroxyethyl methacrylate) with pendants of cinnamate groups (CA) were first introduced onto the surface of up-conversion nanoparticles (UCNP), which were then functionalized with anti-CD20 aptamer to give Apt-pHEMA(CA)@UCNP. After a local or systemic administration of Apt-pHEMA(CA)@UCNP plus the local application of 980-nm NIR laser, the growth of tumor was significantly suppressed with no detectable toxicities. Exploring the superior anti-tumor efficiency of Apt-pHEMA(CA)@UCNP combined with 980-nm NIR laser, we found that Apt-pHEMA(CA)@UCNP bound onto the surface of tumor cell by the interaction between CD20 receptors and anti-CD20 aptamers, without causing any reduction on cell viability. While after the local application of 980-nm laser, UCNP harvested the NIR light and converted it into UV light, which resulted in the cross-linking of CA groups, thus the clustering of CD20 receptors and cell apoptosis. We believe this NIR up-conversion controlled, in-situ synthesized drug-free macromolecular therapeutic expands the repertoire of macromolecular drugs and opens a new avenue for tumor therapy.